Influence of magnetic field on properties of electrodeposited FeCo layer - Tung, Mai Thanh; Anh Dung, Dang Viet; Truong, Nguyen Xuan (Vietnam Journal of Chemistry, 2014)
Effect of magnetic field on the electrodeposition of FeCo layers has been investigated with respect to the orientation of the magnetic field to surface electrode e.g magnetic field is parallel and perpendicular to electrode. Electrochemical behaviours, morphology, composition, structure and magnetic properties were investigated using cyclic voltammogram (CV), Scanning Electron Microscopy (SEM), Energy Dispersion Spectroscopy (EDS), X-Ray Diffractometer (XRD), Vibrating Sample Magnetometer (VSM). Results show that morphology and structure of the deposited layers are not effected by external magnetic field. Meanwhile, the Fe content of the layer decreases by following sequence CFe(B=0)>CFe(B//)>CFe(^), resulting in the following sequence of coerciviy HC(B=0)> HC (B//)> HC (^). These results were explained based on the magnetohydronamic (MHD) effect caused by the Lorentz force () when magnetic field is superimposed.